2010
DOI: 10.3732/ajb.0900064
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and divergence date estimates of a lichen species complex with a disjunct distribution pattern

Abstract: Disjunct species distributions may result from a combination of geologic events and long-distance dispersal. The foliose lichen species complex Leptogium furfuraceum-L. pseudofurfuraceum has an intercontinental disjunction pattern. Populations of this species complex are found in western North America, southern South America, Africa, and southern Europe. We conducted a phylogenetic study to reconstruct the biogeographic history of this species complex using two ribosomal genes (ITS and LSU) and a protein-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 63 publications
4
50
1
Order By: Relevance
“…Other examples are disjunct species in Xanthoparmelia that represent distinct, cryptic species on different continents (Thell et al 2009;Hodkinson and Lendemer 2011) or distinct species on different continents in the genus Physcia ). In the Leptogium furfuraceum-L. pseudofurfuraceum complex sister-group relationships were found between populations from the same hemispheres, incongruent with previous classifications based on morphological differences (Otalora et al 2010). The results of a dating estimate suggest that the species migrated via transoceanic dispersal with subsequent diversification on different continents.…”
Section: Molecular Studies Addressing Species Delimitations In Lichenmentioning
confidence: 62%
“…Other examples are disjunct species in Xanthoparmelia that represent distinct, cryptic species on different continents (Thell et al 2009;Hodkinson and Lendemer 2011) or distinct species on different continents in the genus Physcia ). In the Leptogium furfuraceum-L. pseudofurfuraceum complex sister-group relationships were found between populations from the same hemispheres, incongruent with previous classifications based on morphological differences (Otalora et al 2010). The results of a dating estimate suggest that the species migrated via transoceanic dispersal with subsequent diversification on different continents.…”
Section: Molecular Studies Addressing Species Delimitations In Lichenmentioning
confidence: 62%
“…Our estimation of the substitution rate for the nuLSU of the Parmeliaceae (1.12×10 −9 s/s/y; Table 2) is in the same order of magnitude but slower than in the phytopathogenous fungi of Erysiphales. This indicates that caution should be used when applying substitution rates of a group of fungi to estimate divergence times of an unrelated group [58][59].…”
Section: Discussionmentioning
confidence: 99%
“…d Tephromela atra sensu lato found in the Santa Monica Mountains, California, USA (see Muggia et al 2014) (photograph credit J. Hollinger) ambiguous due to the occurrence of phenotypically similar lichens occurring across broad, intercontinental distributions and uncertainty of appropriate species circumscriptions. While a number of lichen-forming fungal species have been found to be truly widespread (e.g., Lindblom and Søchting 2008;Fernández-Mendoza et al 2011;Ahti and Hawksworth 2005;Del-Prado et al 2013), improved recognition of species boundaries has provided insight into important biogeographical patterns in lichens previously assumed to have cosmopolitan distribution patterns (Leavitt et al 2013d;Del-Prado et al 2013;Amo de Paz et al 2012;Sérusiaux et al 2011;Otálora et al 2010;Elix et al 2009). Cryptic diversity and complex biogeographic patterns are highlighted in the Rhizoplaca melanophthalma species group ( Fig.…”
Section: Species In Lichenized Fungimentioning
confidence: 99%
“…While this iterative approach to species delimitation and taxonomy has proven valuable for understanding species boundaries and describing new taxa in some groups of lichenized fungi, a posteriori examination of morphological and chemical features has failed to reveal diagnostic phenotypic characters in a number of studies (Muggia et al 2014;Leavitt et al 2011a;Otálora et al 2010;O'Brien et al 2009). Furthermore, a study of widespread species in the genus Melanelixia (Parmeliaceae) indicated that phenotypically cryptic lichen-forming fungal species-level lineages may be relatively ancient and diagnosable phenotypic differences may be absent even millions of years after the initial divergence (Leavitt et al 2012b).…”
Section: 3mentioning
confidence: 99%